PENGARUH DAYA TARIK IKLAN PUYO DESSERT SALTED CARAMEL DI MEDIA SOSIAL INSTAGRAM TERHADAP BRANDAWARENESS : Survei Pada Followers Instagram PUYO Dessert - Dinna Sebriana, - (2019)
The development of the era that formed the culture of the city background, making dessert food became fast food. This has become a business opportunity for young people. PUYO Dessert became the first originator of silky pudding in Indonesia. Advertising strategy in conducting promotional activities is to see how the influence of PUYO Dessert ads on social media instagram. This study discusses how the Influence of PUYO Ads Dessert Saltted Caramel on Instagram Social Media Against Awaraness Brand. The purpose of the research in this study was to find out and measure how much influence PUYO Dessert Salted Caramel advertisements on Instagram social media on Awaraness Brand. Research theory uses S-O-R. This research method uses quantitative methods. The sample in this study was PUYO Dessert Instagram followers, which amounted to 100 respondents. The sampling technique used is Simple Random sampling. Data collection techniques using a questionnaire or questionnaire distributed by respondents. The results showed that there were influences on the PUYO advertisement of Dessert Salted Caramel on strong social instagram. Based on the calculation of the results of the determination it is known that the correlation value (r) = 0.719 and nilan R square (which is the correlation value) is = 51.69%. Then it can be concluded that 51.69% Brand awareness (Y variable) PUYO Dessert Instagram followers are determined by the appeal of PUYO dessert salted caramel ads on Instagram social media (Variable X), and the remaining 48.31% is determined by other factors outside of research